Control interno de los costos de los productos terminados de la compañía ALTEC S.A del año 2021 en la ciudad de Babahoyo. - Sandoval Ledesma, Betzy Dayana (2023)
The purpose of this case study is to carry out an internal control questionnaire on the costs of finished products of the company ALTEC S.A of the year 2021 in the city of Babahoyo, through an interview with the accountant of the entity to acquire relevant information on how the company is being carried out, based on the findings found in the audit carried out. Regarding the procedures that are used to determine the profit and losses according to the costing system, identifying the important concepts about internal control, and how important the implementation of this tool is, such as control, and how effective it is. to safeguard the resources and its impact that it would have in terms of the management of the company. To determine the optimal development of the investigation to meet its objectives, based on the processes that must be followed in the correct implementation of internal control, identification, evaluation of the mechanisms that influence management activities, Allowing the processing that is being carried out in the finished products to be adequate, also anticipating any risk that may arise, this will help to reduce the waste caused by not applying it correctly to the production processes, to avoid any minimum waste, and in turn taking advantage of the time as well as the raw material in order to obtain the desired finished product, helping to make good decisions.